2005
DOI: 10.1080/13561820500081802
|View full text |Cite
|
Sign up to set email alerts
|

Academic administrators' attitudes towards interprofessional education in Canadian schools of health professional education

Abstract: Interprofessional education is an approach to educating and training students and practitioners from different health professions to work in a collaborative manner in providing client and/or patient-centred care. The introduction and successful implementation of this educational approach is dependent on a variety of factors, including the attitudes of students, faculty, senior academic administrators (e.g., deans and directors) and practitioners. The purpose of this study was to examine attitudes towards inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 21 publications
2
37
0
1
Order By: Relevance
“…Gaining buy-in from administrators, faculty, and students that IPE is worth the effort may also be difficult [15]. In addition to the aforementioned issues, one study revealed that "turf battles" are another potential problem when implementing IPE activities [16]. If there is no centralized IPE organizational unit directing the activities, academic administrators from the different programs may vie for control of resources and programming, thereby creating a less than ideal atmosphere for collaboration.…”
Section: Challenges Of Interprofessional Educationmentioning
confidence: 99%
“…Gaining buy-in from administrators, faculty, and students that IPE is worth the effort may also be difficult [15]. In addition to the aforementioned issues, one study revealed that "turf battles" are another potential problem when implementing IPE activities [16]. If there is no centralized IPE organizational unit directing the activities, academic administrators from the different programs may vie for control of resources and programming, thereby creating a less than ideal atmosphere for collaboration.…”
Section: Challenges Of Interprofessional Educationmentioning
confidence: 99%
“…There is a growing body of evidence to suggest that IPE is a challenge to faculties who are required to assist in its implementation (Barrett et al 2003;Gilbert 2005;Oandasan & Reeves 2005;Steinert 2005). Curran has shown a polarisation of views, mainly in the medical faculty (Curran et al 2005). Many of the leading advocates who have set up and maintained IPE within the UK curriculum for entire cohorts of a wide range of different disciplines are now reflecting on 10 years or more of these experiences (Barr 2007;Anderson & Lennox 2009) and at faculty level these IPE champions remain a key factor (Glasby & Dickinson 2008).…”
Section: Practice Pointsmentioning
confidence: 99%
“…10,20,31 Too often, however, the CIs interviewed did not perceive IPE as an integral part of direct patient care. When IPE is seen to be truly valued, CIs will successfully offer this experience to their students.…”
Section: Discussionmentioning
confidence: 99%
“…10 A high level of support for the concept and principles of IPE and collaborative patient care is required if academic IPE programmes are to be successful. Identified barriers to implementing academic IPE include rigid curricula, ''turf battles'' between various health care disciplines, lack of perceived value, 10 ''academic elitism,'' and a ''siloed'' approach to education. 1 Research has also demonstrated that students embrace opportunities for IPE and reap benefits in the realms of knowledge, skills, and attitudes.…”
Section: Literature Reviewmentioning
confidence: 99%